Neutrosophic Set Theory in E-Commerce Evaluation: A Novel Approach to Sales Strategy Optimization - Benjhall Jordan Camargo Vilcapoma; Valia Ximena Huaman Coras; Rosa María Criollo Delgado (Neutrosophic Sets and Systems)
In practical terms, the most accurate term to use is “language economy”, which translates as contemporary languages. It is possible to infer that language interacts indirectly with people’s lives, influencing their way of socializing and lifestyle. The common population maintains constant contact with various foreign languages, instinctively collecting elements, which favors the development of the person. However, it is logical to propose the inclusion of language economy in scientific and cultural theoretical debates at a general level. It will be an example of building connections between theory and practice. Language, in its primary role of communication, contains the concepts of a society that is always in constant change. Language, considered a relevant social element, is in constant transformation: evolving and adjusting to people’s demands. This method theoretically contributes to improving existing analytical models and, in practical terms, proposes concrete actions aimed at optimizing digital platforms, optimizing the user experience and increasing efficiency in operations. Finally, the study not only fills a methodological gap in the field of e-commerce, but also proposes a tactic for companies to use its benefits in a constantly changing and competitive global context.